Pola dan Implikasi Sikap Partisan terhadap Estetika Trilogi Novel â€œKemiâ€ Karya Adian Husaini (Patterns and Implications of Partisan Attitudes to the Aesthetics of Adian Husaini's â€œKemiâ€ Novel Trilogy) - Liana Shinta Dewi; Winasti Rahma Diani; M. Dhaniel Fahmi Rizal (Jurusan Tadris Bahasa Indonesia, 2022)
This study aims to understand the partiality of Kemi trilogy by Adian Husaini and its impact on the aesthetic of the novel. This is a quantitative study using a methodology of aesthetics established by Dewit H. Parker. The result shows two patterns of partiality. First, the author ignores the